The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1093/ajcn/56.1.297s
|View full text |Cite
|
Sign up to set email alerts
|

High-density-lipoprotein metabolism during a very-low-calorie diet

Abstract: We examined the changes in high-density-lipoprotein (HDL) metabolism in eight female obese patients undergoing a very-low-calorie diet (VLCD). In the first half of the study, HDL cholesterol (HDL-C), apolipoprotein A-I (apo A-I), and apo A-II showed a parallel decrease. Although lipoprotein lipase (LPL) and hepatic lipase (HTGL) did not change, lecithin: cholesterol acyltransferase (LCAT) decreased. In the latter half of the protocol, HDL-C and apo A-I increased whereas apo A-II decreased, resulting in increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
1
7
0
1
Order By: Relevance
“…HDL 2 , Apo A-I, and pre- β 1 are associated with cardioprotection and are found to be reduced in the obesity [35]. In response to the VLCD, Shoji et al [29] observed that the initial decrease in HDL 2 was associated with decreased lecithin cholesterol ester transfer protein (LCAT) (which plays an important role in the formation of HDL 2 [36]) while Apo A-1 increased. Apo A-1 activates LCAT, which may explain the delayed improvement in HDL [29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…HDL 2 , Apo A-I, and pre- β 1 are associated with cardioprotection and are found to be reduced in the obesity [35]. In response to the VLCD, Shoji et al [29] observed that the initial decrease in HDL 2 was associated with decreased lecithin cholesterol ester transfer protein (LCAT) (which plays an important role in the formation of HDL 2 [36]) while Apo A-1 increased. Apo A-1 activates LCAT, which may explain the delayed improvement in HDL [29].…”
Section: Discussionmentioning
confidence: 99%
“…The energy intake from VLCDs ranged from 400–600 kcal/d. Two studies included women only [29] and one study included type 2 diabetic patients only [30]. The format of the different interventions varied widely, and is described in more detail in Table 3.…”
Section: Effect Of Intermittent Use Of Vlcd On Hdl Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…HDL cholesterol responses are not that uniform: several studies documented a decrease of HDL cholesterol levels [70,73,[76][77][78][79] when lipid profiles were measured within the first 2 to 8 weeks of VLCDs. Others report increases in HDL cholesterol, but in these studies lipid profiles were measured later, at about 3 to 12 months into the VLCD program [72,74,79]. HDL cholesterol responses appear to be biphasic.…”
Section: Effects Of Very Low-calorie Diets On the Lipid Profilementioning
confidence: 99%